A study on risk management at case study theme park / Siti Salmah Taslim - Taslim, Siti Salmah (Faculty of Architecture, Planning and Surveying, 2013)
In Malaysia, country with the famous sights of beautiful and interesting with the Prime Minister of Malaysia the fourth Tun Dr. Mathatdir Mohammad have organized a campaign ‘Cuti-Cuti Malaysia’. While Malaysia also has the largest the park in Asia as Genting Highland in Pahang, Sunway Lagoon Theme Park at Subang Jaya,Selangor, Lost of Tambun at Ipoh Perak. That has attracted the attention of visitors’, whether from within the country and form abroad to experience the jot the park. In addition, there are more theme parks which attract visitors such as wet world also have also have a branches in several places in Malaysia such as water world at Melaka, Bukit Merah Lake Town Resort at Taiping Perak, and the new theme park are launching on the last year is a Bukit Gambang Water Park at Kuantan Pahang and Legoland Malaysia at Johor Bahru